EFEKTIVITAS PEMERIKSAAN PAJAK TERHADAP WAJIB PAJAK YANG MELAKUKAN PERLAWANAN PAJAK DITINJAU DARI SISI FISKUS (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA BATU) - Descalaya, Mada Vita (Jurnal Mahasiswa Perpajakan, 2014)
For the state taxes are one of the important sources of acceptance that will be used to finance state expenditure. In contrast to the company, the tax is burden would reduce earning after tax. Many attempts were made​​ by the tax payer in an attempt to reduce their tax payment called tax evasion and tax avoidance, until damage of the country. It needs a tax audit function to test compliance and provide a deterrent effect to tax payers who do the tax resistance. The problems that are the object of discussion, that how the level of effectiveness of tax audits to tax payers who make tax resistance at KPP Batu from the side of tax authorities. Research used the qualitative descriptive method. Data collection used are sources of primary data is an interview to the tax authorities, and sources of secondary data are documents required. From the interviews showed that the implementation of the inspection on the KPP Batu has been in accordance with existing regulations. According to the tax authorities KPP Batu, we know that so far tax audits has been effective to tax payer which do the Tax Avoidance and Tax Evasion. This is reinforced by the data obtained from the 2010-2013 in a row shows the effectiveness of 98,97%; 97,94%; 97,06%; 100%. Keywords: effectiveness, tax audits, tax resistance